Generation of a Murine Model for c-MYC and BCL2 Co-expression B Cell Lymphomas - Cai, Zhenming; Zhang, Le; Cao, Min; Wang, Yuliang; Wang, Feng; Bian, Weiqi; Zhai, Sulan; Wang, Xiaoming (Frontiers in Oncology, 2020)
Diffuse large B-cell lymphoma (DLBCL), the most frequent lymphoma in adults, is a clinically and biologically heterogeneous group of lymphomas associated with diverse response to therapy. c-MYC and BCL2 play important roles in normal B-cell differentiation and tumorigenesis. B cell lymphoma with dual expression of c-MYC and BCL2 (double-expressor lymphoma, DEL) accounts for approximately one-third of DLBCL cases. DEL patients have poor outcomes after chemoimmunotherapy or autologous stem-cell transplantation. Lack of a genetic mouse tool for DEL hinders us from understanding the lymphogenesis mechanism and developing therapeutic strategies. Here, we investigated whether ectopic expression of c-MYC and BCL2 in different stage B cells could lead to lymphoma and generate a mouse model for DEL. We observed that coexpression of c-MYC and BCL2 in germinal center (GC) B cells, or pan-B cells could induce B-cell lymphomas. The tumor-bearing mice have enlarged lymphoid organs, and B cells massively infiltrate into non-lymphoid organs including lung, liver and kidney. The tumor-bearing mice manifested significantly shortened lifespan than the controls. In addition，adoptively transfer of coexpression B cells leads to B cell lymphoma and donor mouse death. This model provides us a tool to explore the pathogenesis and treatment of DEL.